أثر الحوكمة المصرفية على الأداء المالي في البنوك التجارية دراسة عينة من بنوك ولاية ورقلة - بوقفة, عبد الحق; عيساوي, سهام; محمدي, خليدة (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة الى البحث في أثر الحوكمة المصرفية على الاداء المالي للبنوك التجارية وذلك من خلال مؤشرات الافصاح والشفافية ومهام ومسؤوليات مجلس الادارة، وللوصول إلى ذلك قمنا بتوزيع استبيان على مجموعة من الموظفين في عينة من البنوك التجارية بولاية ورقلة. وقد توصلنا الى مجموعة من النتائج أهمها أن مختلف مبادئ الحوكمة لها علاقة طردية وموجبة بالأداء المالي في البنوك التجارية محل الدراسة لاسيما الافصاح والشفافية ومسؤوليات ومهام مجلس الادارة و بالتالي فالحوكمة المصرفية لها أثرا فعالا على تحسين الاداء المالي للبنوك التجارية . Abstract: This study aimed to investigate the impact of banking governance on the financial performance of commercial banks, through disclosure and transparency indicators, and the duties and responsibilities of the board of directors. We have reached a set of results, the most important of which is that the various principles of governance have a direct and positive relationship with the financial performance of the commercial banks under study, especially disclosure, transparency, responsibilities and tasks of the board of directors, and therefore banking governance has an effective impact on improving the financial performance of commercial banks.
The impact of banking governance on the financial performance of commercial banks, a study of a sample of banks in the state of Ouargla
مقال
Keywords: حوكمة مصرفية ; اداء مالي ; افصاح و شفافية